Integrative transcriptome profiling for identifying ALS potential treatment using the drug repurposing approach - Navid Kashani; Amir Sabbaghian; Fatemeh EmamiPari; Mohammad Khalili Gorjimahalleh; Mahdi Aalikhani (Egyptian Journal of Medical Human Genetics)
Abstract Background Amyotrophic lateral sclerosis (ALS), an alarming neurodegenerative disorder, induces muscle atrophy and motor deterioration. The current treatments exhibit limited improvement in survival rates. Thus, we here attempted to identify crucial genetic biomarkers through transcriptome profiling and systems biology methodologies to advance our knowledge of the diagnosis and pathogenesis of ALS. Following this, a drug repurposing approach was employed to introduce possible treatments for ALS. Results After analyzing differentially expressed genes (DEG) using different in silico approaches, 43 DEGs (23 upregulated and 20 downregulated) were identified, which were abnormally expressed in ALS patients compared to healthy individuals. Two proteins CMPK2 and IFI44L were identified as ALS biomarkers and selected for molecular docking. Then, molecular docking was performed to repurpose drugs that have the potential to suppress upregulated proteins. Accordingly, three drugs including ketoprofen, thalitone, and cromolyn have been repurposed against CMPK2 and IFI44L proteins. Conclusions CMPK2 and IFI44L serve as potential biomarkers for ALS and may be applied in the diagnostic assessment of this disorder within the bloodstream of affected individuals. Furthermore, three drugs were proposed as potential therapeutic candidates for ALS with the help of transcriptomics profiling. We advocate for the implementation of these identified pharmacotherapies in animal models of ALS to validate their therapeutic efficacy. This approach also would help narrow down the options to more suitable targets and economically viable treatments.